Bullying victimization and stress sensitivity in help-seeking youth: findings from an experience sampling study - Rauschenberg, Christian; van Os, Jim; Goedhart, Matthieu; Schieveld, Jan N. M.; Reininghaus, Ulrich (European child & adolescent psychiatry, 2021)
Bullying victimization confers the risk for developing various mental disorders, but studies investigating candidate mechanisms remain scarce, especially in the realm of youth mental health. Elevated stress sensitivity may constitute a mechanism linking bullying victimization and mental health problems. In the current study, we aimed to investigate whether exposure to bullying victimization amplifies stress sensitivity in youth’s daily life. The Experience Sampling Method (ESM) was used to measure stress sensitivity [i.e. the association of momentary stress with (i) negative affect and (ii) psychotic experiences] in 42 help-seeking youths (service users), 17 siblings, and 40 comparison subjects (mean age 15 years). Before ESM assessments, bullying victimization at school as well as various psychopathological domains (i.e. depression, anxiety, psychosis) were assessed. Service users exposed to high levels of overall (primary hypotheses) as well as specific types (secondary hypotheses; physical and indirect, but not verbal) of bullying victimization experienced more intense negative affect and psychotic experiences in response to stress compared to those with low exposure levels (all p < 0.05), whereas, in contrast, controls showed either less intense negative affect or no marked differences in stress sensitivity by exposure levels. In siblings, a less consistent pattern of findings was observed. Findings suggest that stress sensitivity may constitute a potential risk and resilience mechanism linking bullying victimization and youth mental health. Interventions that directly target individuals’ reactivity to stress by providing treatment components in real-life using mHealth tools may be a promising novel therapeutic approach.